1990
DOI: 10.1177/105381519001400405
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Employee Stability and Turnover in Home-Based Early Intervention

Abstract: Unusually high turnover rates in early intervention programs will contribute significantly to the documented shortage of qualified personnel needed for the successful implementation of PL 99-45 7, forcing policy makers to consider options for maximizing the retention of personnel presently in the field. This study was conducted to provide an initial indication of the extent of turnover among early childhood interventionists working in a statewide network of home-based early intervention programs. Results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…7 There is evidence to indicate that workplace interventions are effective at targeting multiple health and productivity outcomes including improving healthy behaviors, [8][9][10] physical health, 11,12 mental health, [13][14][15] disability, 16 and preventing absenteeism, [17][18][19] presenteeism, 15,17 and employee turnover. 20,21 Although many employers are now increasingly concerned about the cost burden driven by health care and loss of productivity, the major focus behind their efforts is to prevent disease and slow the progression of chronic conditions. Commonly used workplace assessment tools such as the Health and Work Performance Questionnaire (HPQ) 22 and the Work Productivity and Activity Impairment Questionnaire were created based on this perspective.…”
Section: Introductionmentioning
confidence: 99%
“…7 There is evidence to indicate that workplace interventions are effective at targeting multiple health and productivity outcomes including improving healthy behaviors, [8][9][10] physical health, 11,12 mental health, [13][14][15] disability, 16 and preventing absenteeism, [17][18][19] presenteeism, 15,17 and employee turnover. 20,21 Although many employers are now increasingly concerned about the cost burden driven by health care and loss of productivity, the major focus behind their efforts is to prevent disease and slow the progression of chronic conditions. Commonly used workplace assessment tools such as the Health and Work Performance Questionnaire (HPQ) 22 and the Work Productivity and Activity Impairment Questionnaire were created based on this perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in human service professions have shown that staff training can be an effective tool against burnout, feelings of isolation, overload, and staff frustration (Palsha, Bailey, Vandiviere, & Munn, 1990;Spell et a l , 1993). However, if the type of training advocated here is to be funded as a support service for persons with severe disabilities, additional research is needed to specifically document the effects of such training on the communication of those individuals.…”
Section: Need For Efficacy Researchmentioning
confidence: 99%
“…National shortages of highly qualified personnel in the fields of early intervention (EI), and early childhood special education (ECSE) are well documented in the professional literature (Dymond, Gilson, & Myran, 2007; Hebbeler, 1994; National Early Childhood Technical Assistance Center [NECTAC], 2011; Palsha, Bailey, Vandiviere, & Munn, 1990; U.S. Department of Education [DOE], Office of Postsecondary Education, 2016), and are likely to persist (McLeskey & Billingsley, 2008; McLeskey, Tyler, & Flippin, 2003; U.S.…”
mentioning
confidence: 99%